Post-colonial Literature- Valorization of Local Identities through Code Switching - Langah, Nukhbah Taj; David, Maya Khemlani; Ali, Ameer (Journal of Research in Humanities, 2023)
This study analyzes postcolonial literature, with a focus on the strategy of code-switching. During the colonial era, Southeast Asian and South Asian countries, such as Malaysia, Pakistan, India, and Bangladesh, faced the hegemonic structures and values imposed by European countries. This resulted in the degradation of local identities, languages, norms, and values. Consequently, in the post-colonial era after independence, many postcolonial writers started questioning the colonial legacy in their literary works. Critics and theorists, such as Homi K. Bhabha, and Gayatri Spivak influenced the post-colonial thought that sought to valorize local identities. This study seeks to investigate this process of valorization. Our discussion is focused on selected examples taken from a contemporary writer, Wajahat Ali’s play, The Domestic Crusaders (2011) . Valorization is identified as a process of giving value or merit to a person, thing, or idea. Our primary focus in this paper is on how the writer gives value and merit to local identities through the use of code-mixing/codeswitching. Furthermore, we argue that this valorization challenges colonial structures and norms. To conduct a thematic analysis, a purposive sampling technique was adopted to collect data from this fictional text.